Altered dynamics of mitochondria and reactive oxygen species in the erythrocytes of migrating red-headed buntings - Bhardwaj, Nitin; Kumar, Anit; Gupta, Neelu Jain (Frontiers in Physiology, 2023)
Background: Blood antioxidants provide propensity to mitigate reactive oxygen species (ROS) apart from other oxidative challenges during a high-energy state of migration in night migratory songbirds. The study investigated the modulation of erythrocytes, mitochondrial abundance, hematocrit changes, and relative expression of fat transport-related genes during migration in red-headed buntings (Emberiza bruniceps). We hypothesized an increase in antioxidants along with the mitigation of mitochondria-related reactive oxygen species elevation and consequential apoptosis occurring during migration. Methods: Male red-headed buntings (n = 6) were placed under short days (8 h of light and 16 h of dark, 8L:16D)/long days (14L:10D) and photo induced to simulated non-migratory, nMig; pre-migratory, pMig; and migratory, Mig, states. Erythrocyte shape, reactive oxygen species production, mitochondrial membrane potential (MMP), reticulocyte proportion, and apoptosis were analyzed using flow cytometry and relative expression of fat metabolizing and antioxidant genes was measured by using qPCR. Results: There was a significant increase in hematocrit, erythrocyte area, and mitochondrial membrane potential. Reactive oxygen species and apoptotic erythrocyte proportion declined in the Mig state. The changes in antioxidant genes (SOD1 and NOS2), fatty acid translocase (CD36), and metabolic (FABP3, DGAT2, GOT2, and ATGL) genes showed a significant increment during the Mig state. Conclusion: These results suggested that adaptive changes occur in mitochondrial behavior and apoptosis of erythrocytes. The transition in erythrocytes, antioxidant genes, and fatty acid metabolism gene expressions suggested differences in regulatory strategies at the cellular/transcriptional level during different states of simulated migration in birds.